2020
DOI: 10.4103/ijpsym.ijpsym_238_19
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use, Mental Health, and Sleep Quality among Medical Students: A Path-Analytic Model

Abstract: Background: There is a close association between problematic Internet use (PIU), sleep quality, and mental health problems. To evaluate which mental health problem is more associated with coexistence of both PIU and poor sleep quality, we hypothesized a model in which PIU influences sleep quality directly and also through the mediation of three different mental health problems. Methods: A total of 402 medical students completed the Persian versions of the Internet Addiction Test, 21-item Depression Anxiety Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 37 publications
4
43
0
7
Order By: Relevance
“…18 Several studies have found that internet addiction increases the risk of depression, anxiety and stress. [16][17][18][19] Due to the sudden onset of COVID-19, few studies have explored the effects of SARS-COV-2 on mental health. 14,20,21 To our knowledge there are no studies in Latin American countries that have explored how this pandemic may increase internet addiction, and its relationship to triggering anxiety and depression in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…18 Several studies have found that internet addiction increases the risk of depression, anxiety and stress. [16][17][18][19] Due to the sudden onset of COVID-19, few studies have explored the effects of SARS-COV-2 on mental health. 14,20,21 To our knowledge there are no studies in Latin American countries that have explored how this pandemic may increase internet addiction, and its relationship to triggering anxiety and depression in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Internet addiction has been defined as excessive or poorly controlled preoccupations, urges, or behaviors regarding computer use and internet access that lead to impairment or distress. [ 1 2 ] Internet addiction can cause neurological complications, anxiety, depression, and can affect the academic performance of university students. [ 1 ] The previous studies in the United States and Europe found a prevalence rate between 1.5% and 8.2%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] Internet addiction can cause neurological complications, anxiety, depression, and can affect the academic performance of university students. [ 1 ] The previous studies in the United States and Europe found a prevalence rate between 1.5% and 8.2%. [ 3 ] In the previous studies from the Middle East and Asia, the prevalence of internet addiction among adolescent and university students varies from 0.9% to as high as 33%.…”
Section: Introductionmentioning
confidence: 99%
“…However, they were not able to conclude due to conflicting findings regarding the effect of problematic mobile use on obesity risk, sleep duration and physical activity. In a related study, Shadzi et al (2020) found that PIU may not result in adverse health-related outcomes, such as sleep disturbances and mental health issues. Therefore, this research proposes that: H 1 : Problematic internet use positively influences adverse health outcomes.…”
Section: Problematic Internet Use and Negative Health Outcomesmentioning
confidence: 96%
“…Prior research on the relationship between PIU and adverse health outcomes has yielded contradictory and inconsistent findings (An et al, 2014;Bener et al, 2011;Canan et al, 2013;Choi et al, 2009;Domoff, Borgen, Foley, & Maffett, 2019;Gámez-Guadix, 2014;Ostovar et al, 2016;Shadzi, Salehi, & Vardanjani, 2020;van Deursen, Bolle, Hegner, & Kommers, 2015). To address these inconsistencies, we used a moderator variable in the relationship between PIU and adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%